Political identity in South Asia/ edited by David Taylor and Malcolm Yapp - Taylor, David (ed.); Yapp,Malcolm. (ed.) (London, 1979)
This volume deals with the relationship between language, religion and political identity. Political identity is a broader concept than that of nationalism which it embraces, and the contributors are concerned with a wide range of political phenomena in South Asia. Primary atten tion is paid to linguistic and religious factors in the making of political identities and the formulation of new political demands, but the operation of these factors is seen as being conditioned and in some cases determined by grander political and economic forces. Within this framework, three papers are particularly concerned with Muslims in South Asia, and three with southern India, where language has played an important part. Two papers are studies of Bangladesh and Sri Lanka, and one is concerned with tribal populations in India. The volume is completed by two more general essays on the subject of political identity.
Keywords: South Asia - Politics and Government. 2 Language - Polit